Muscle strength assessment of knee flexors and extensors. Comparative study between basketball, football, handball and volleyball athletes - Teixeira, J.; Carvalho, P.; Moreira, C.; Carneiro, A.; Santos, R. (International Journal of Sports Science, 2015)
Muscle strength of lower limbs is considered a key factor in handball, basketball, football and volleyball athletes` performance, as support of specific motor skills and actions. One of the methods used to assess muscle strength is isokinetic dynamometry.